Tutor Interventions in Distance Learning - Richardson, Paul; Liber, Oleg (Proceedings of the International Conference on Networked Learning, 2002)
In this paper, we discuss the conditions which are necessary for active engagement of students in electronic conferences. We outline results from three modules of a part-time distance degree, where engagement has approached 100%, and describe the type of tutor practice which we believe leads to high levels of student participation.